Sujeto, tiempo e historia en la poesía de Magdalena Chocano - Ruiz Echegaray, Matías (Pontificia Universidad Católica del Perú, 2024)
This paper analyses Magdalena Chocano's book of poems Objetos de distracción (2016) in dialogue with her earlier books Poesía a ciencia incierta (1982) and Estratagema en claroscuro (1986). The aim is to identify and explore the different ways in which the notions of subject, time and history are represented in this work. It is argued that Chocano's poetry questions the conventions of representation of the poetic subject, time and history. It shows the transition from the construction of a paradoxical subject —visionary and vulnerable— to a decentralised voice without identity marks. It also investigates the configuration of a discontinuous temporality in the author's later poetry, which shares with her earlier works the rejection of a homogeneous and linear time. It is proposed that her poetry shows a fragmentary and discontinuous vision of history, against the current of epic or totalising discourses

El trabajo analiza el libro de poemas Objetos de distracción (2016) de Magdalena Chocano en diálogo con sus primeros libros Poesía a ciencia incierta (1982) y Estratagema en claroscuro (1986). El propósito es identificar y explorar las distintas formas en que las nociones de sujeto, tiempo e historia se representan en esta obra. Se sostiene que la poesía de Chocano plantea un cuestionamiento de las convenciones de representación del sujeto poético, del tiempo y de la historia. Se observa el paso de la construcción de un sujeto paradójico —visionario y vulnerable— a una voz descentrada y sin marcas de identidad. Se indaga asimismo en la configuración de una temporalidad discontinua en la poesía última de la autora, que comparte con sus primeros trabajos el rechazo a un tiempo homogéneo y lineal. Se propone que su poesía muestra una visión fragmentaria y discontinua de la historia, a contracorriente de los discursos épicos o totalizantes.
Subject, time and history in the poetry of Magdalena Chocano
Keywords: Magdalena Chocano; Contemporary Peruvian Poetry; Discontinuity; History; Magdalena Chocano; Poesía peruana contemporánea; Discontinuidad; Historia; https://purl.org/pe-repo/ocde/ford#6.02.05